2004
DOI: 10.1007/s00466-003-0543-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of material forces in adaptive finite element methods

Abstract: The theory of material forces for a hyperelastic material is briefly presented using the translational invariance of the control volume. The theory is derived for the dynamical setting, while the numerical implementation is limited to the static case. The finite element (FE) method is used to solve the standard field equations. After obtaining the solution the material force balance is consistently discretized with FE. As a result of this postprocessing discrete material forces are obtained. They are then used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…In this section, the concept of material forces and a finite element-based technique to evaluate material forces is reviewed. For a detailed discussion on material forces, we point to References [14][15][16][17] and to see its application within finite elements the interested reader can refer to References [18,41,42]. …”
Section: Materials Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the concept of material forces and a finite element-based technique to evaluate material forces is reviewed. For a detailed discussion on material forces, we point to References [14][15][16][17] and to see its application within finite elements the interested reader can refer to References [18,41,42]. …”
Section: Materials Forcesmentioning
confidence: 99%
“…Residual-based error estimators measure the error by evaluating the local residual of the differential equation on the element domain and evaluating the flux jump across the element boundaries [13]. Material forces are associated with the Eshelby stress tensor [14][15][16][17], and have been recently used as an error indicator in finite element analysis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Material Force Method has some roots in the contribution [3] which showed that the gradient of the discrete potential energy with respect to the material node point positions can be expressed in terms of the Eshelby stress tensor and which already denoted the components of the gradient associated with the nodes as discrete configurational forces. In [19][20][21] the application of the Material Force Method has been investigated, e.g., in the context of adaptivity, fracture mechanics, and inhomogeneities.…”
Section: Materials Force Methodsmentioning
confidence: 99%
“…Many recent impressive developments are in the application of concepts from configurational mechanics to computational mechanics, see, e.g., [17][18][19][20][21][22]31]. Our own contributions to the field are, e.g., [1,2,4,6,14,[23][24][25][26][27][28][29][30]32].…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the so called r-adaptive FE mesh refinement strategy which was introduced by Braun (1997) [1]. According to definition the configurational force [4] should be zero in the interior of the material when the material is assumed to be homogeneous and isotropic [6]. However, in case of finite element computation this requirement won't be fulfilled and nodal configurational forces appear on interior nodes too.…”
Section: Introductionmentioning
confidence: 99%